2020
DOI: 10.1289/ehp5907
|View full text |Cite
|
Sign up to set email alerts
|

Household Fuel Use and the Risk of Gastrointestinal Cancers: The Golestan Cohort Study

Abstract: BACKGROUND: Three billion people burn nonclean fuels for household purposes. Limited evidence suggests a link between household fuel use and gastrointestinal (GI) cancers. OBJECTIVES: We investigated the relationship between indoor burning of biomass, kerosene, and natural gas with the subsequent risk of GI cancers. METHODS: During the period 2004-2008, a total of 50,045 Iranian individuals 40-75 years of age were recruited to this prospective population-based cohort. Upon enrollment, validated data were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 43 publications
0
26
1
Order By: Relevance
“…The Golestan cohort study from northeast Iran showed higher risk of gastrointestinal cancers in those who were exposed to biomass combustions from cooking and heating, without chimneys. 21 In our study, occupations that previously evaluated by the IARC monographs working groups and classified as 'carcinogenic to humans' (group 1) in relation to lung cancer; such as painter, welder, textile industry workers or having worked as rubber industry workers was not associated with excess lung cancer risk. 13 24 38-40 The reason of no association for these occupations could be the small sample size, and that the small numbers did not allow to evaluate the risk separately in various groups with different levels of exposure, for example, painters in construction industry, or automobile industry painters.…”
Section: Discussionmentioning
confidence: 59%
“…The Golestan cohort study from northeast Iran showed higher risk of gastrointestinal cancers in those who were exposed to biomass combustions from cooking and heating, without chimneys. 21 In our study, occupations that previously evaluated by the IARC monographs working groups and classified as 'carcinogenic to humans' (group 1) in relation to lung cancer; such as painter, welder, textile industry workers or having worked as rubber industry workers was not associated with excess lung cancer risk. 13 24 38-40 The reason of no association for these occupations could be the small sample size, and that the small numbers did not allow to evaluate the risk separately in various groups with different levels of exposure, for example, painters in construction industry, or automobile industry painters.…”
Section: Discussionmentioning
confidence: 59%
“…Previously, we presented preliminary data linking biomass fuel use with increased risk of oesophageal and stomach carcinogenesis [15,21]. An Iranian prospective cohort study of up to 50,045 participants reported that household burning of biomass fuels increased the risk of digestive tract cancers among individuals [22]. There is an urgent need for experimental studies (involving both human and animal models) to identify internal dose carcinogenic biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests that indoor biomass burning is associated with lung cancer risk [56,57]. Robust evidence has been provided that biomass smoke from household cooking and heating is also associated with higher risks of gastrointestinal cancers [58][59][60]. Furthermore, indoor wood-burning stoves were suggested to be associated with a modestly increased risk of breast cancer in the Sister Study from the US [61].…”
Section: Plos Medicinementioning
confidence: 99%